Features kompetentnosnogo approach to the organization of independent learning activities of students in a foreign language - Гаврилюк, О. О.; Іванова, В. В. (Educational Dimension, 2012)
Gavrilyuk O., Ivanovа V. Features kompetentnosnogo approach to the organization of independent learning activities of students in a foreign language. The article deals with the content and meaning of competence approach concerning the organization of the students’ independent educational activities at higher pedagogical institutions. The notion “key competence” is illuminated and the main components of the students’ independent educational activities are analysed.